2006
DOI: 10.1063/1.2190248
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear stability of a charged electrified viscous liquid sheet under the action of a horizontal electric field

Abstract: In a recent paper [D. T. Papageorgiou and P. G. Petropoulos, J. Eng. Math. 50, 223 (2004)] we considered the linear stability of a two-dimensional incompressible leaky dielectric viscous liquid sheet surrounded by a hydrodynamically passive conducting medium, when an electric field is applied parallel to the initially flat bounding fluid interfaces. It was established that for order-one Reynolds numbers and when the dielectric permittivity ratio, εp=εin∕εout, and the electric conductivity ratio, σR=σout∕σin, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
22
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 27 publications
1
22
0
Order By: Relevance
“…3, where h i is the interfacial shape of each low-order model, and h DNS 337 is the output of the direct numerical simulations. Previous studies [19,30] have shown that the 338 critical governing parameters for the stability of the system are the ratios of the permittivities and we will investigate it in more detail in Sec. V. We find that in fact the simplified models provide better 346 accuracy than the regularized models.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…3, where h i is the interfacial shape of each low-order model, and h DNS 337 is the output of the direct numerical simulations. Previous studies [19,30] have shown that the 338 critical governing parameters for the stability of the system are the ratios of the permittivities and we will investigate it in more detail in Sec. V. We find that in fact the simplified models provide better 346 accuracy than the regularized models.…”
mentioning
confidence: 99%
“…This has included work on the full leaky dielectric formulation [17,18] 40 as well as the simpler situations where both regions have large conductivities [19], or indeed where 41 one region is a perfect conductor [20]. Notably, given a permittivity ratio R and a conductivity ratio…”
mentioning
confidence: 99%
“…is also important, this being the cylindrical analogue of the term (σ * /σ − 1) noted by Ozen et al (2006b). The growth rate, Re(s), is a quadratic in k 2 with a double root at k 2 = 0.…”
Section: Asymptotic Propertiesmentioning
confidence: 98%
“…In a cylindrical geometry there are fewer leaky dielectric analyses, consideration mainly being restricted to situations where one fluid is a perfect insulator or conductor (Wang, Mählmann & Papageorgiou 2009;Wang & Papageorgiou 2011), or a jet rather than an annular region (Mestel 1994;Gañán-Calvo 1997;Shin et al 2001;Gañán-Calvo & Montanero 2009). Notably, given a permittivity ratio R and a conductivity ratio σ R between the two regions, the two dimensionless groupings (1 − σ R / R ) and (1 − σ 2 R / R ) have previously been shown to be critical to determining whether the electric field is linearly stabilizing or destabilizing (Ozen et al 2006a;Ozen, Papageorgiou & Petropoulos 2006b). In addition, extensive consideration has been given to electrified jets, albeit this time in the presence of electrokinetic effects (Conroy et al 2011a,b).…”
Section: Introductionmentioning
confidence: 99%
“…The applied interest in studying the liquid surface dynamics in external electric field is related to the possibility of controlling the behavior of liquid surfaces and suppressing hydrodynamic instabilities [7][8][9][10]. The features of the nonlinear evolution of capillary waves at the liquid interfaces in the presence of the horizontal field were analyzed in [11][12][13]. It has been shown in [14][15][16] that, in the case of a strong electric field (the effects of gravitational and capillary forces are negligibly small), nonlinear waves on the surface of a liquid with high dielectric constant can propagate without distortions along (or against) the field direction.…”
Section: Introductionmentioning
confidence: 99%